Virtual Reality and Embodiment in Multimodal Meaning Making. (July 2022) - Mills, Kathy A.; Scholes, Laura; Brown, Alinta
Immersive virtual reality (VR) technology is becoming widespread in education, yet research of VR technologies for students' multimodal communication is an emerging area of research in writing and literacies scholarship. Likewise, the significance of new ways of embodied meaning making in VR environments is undertheorized—a gap that requires attention given the potential for broadened use of the sensorium in multimodal language and literacy learning. This classroom research investigated multimodal composition using the virtual paint program Google Tilt Brush™ with 47 elementary school students (ages 10–11 years) using a head-mounted display and motion sensors. Multimodal analysis of video, screen capture, and think-aloud data attended to sensory-motor affordances and constraints for embodiment. Modal constraints were the immateriality of the virtual text, virtual disembodiment, and somatosensory mismatch between the virtual and physical worlds. Potentials for new forms of embodied multimodal representation in VR involved extensive bodily, haptic, and locomotive movement. The findings are significant given that research of embodied cognition points to sensorimotor action as the basis for language and communication.